2022
DOI: 10.3389/fonc.2021.794959
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog−Gli2 Signaling Promotes Chemoresistance in Ovarian Cancer Cells by Regulating MDR1

Abstract: BackgroundCisplatin (DDP) resistance remains a key challenge in improving the clinical outcome of patients with ovarian cancer (OC). Gli2 overexpression can lead to DDP resistance in OC cells, but the specific underlying regulatory mechanism remains unclear. The membrane transporter encoding gene MDR1 positively regulates chemotherapy resistance in various cancer types. We evaluated MDR1 as a potential Gli2 downstream target and the contribution of the Gli2/MDR1 axis in promoting DDP resistance in OC cells.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Western blot analysis was performed to evaluate the expression of drug resistance-related proteins caused by the different treatments. We found that free CDDP exhibited no significant effect on MDR1 expression, resulting in multidrug resistance. Free Nira, MCT, and MNT moderately reduced MDR1 expression, and the effect of MNCT was the most significant owing to the synergistic effect of Nira. In the SKOV3 DDP cells, the drug-loaded NPs exhibited a higher decrease in MDR1 expression than the single free drugs.…”
Section: Resultsmentioning
confidence: 82%
“…Western blot analysis was performed to evaluate the expression of drug resistance-related proteins caused by the different treatments. We found that free CDDP exhibited no significant effect on MDR1 expression, resulting in multidrug resistance. Free Nira, MCT, and MNT moderately reduced MDR1 expression, and the effect of MNCT was the most significant owing to the synergistic effect of Nira. In the SKOV3 DDP cells, the drug-loaded NPs exhibited a higher decrease in MDR1 expression than the single free drugs.…”
Section: Resultsmentioning
confidence: 82%
“…The DDP dose was increased from 50 ng/mL to a maximum of 1000 ng/mL (50, 100, 150, 200, 300, 500, 800, and 1000 ng/mL) as described in the previous study. 16 The DDP-resistant cell strain, labeled as A2780/DDP, was maintained in RPMI1640 complete medium containing 1 µg/mL DDP. During 48 h, 2.5, 5, 10, 20, or 40 μM Baohuoside I (Selleck) was added to both A2780 and A2780/ DDP cells.…”
Section: Methodsmentioning
confidence: 99%
“…After 3 days of DDP therapy (3‐day treatment cycles), the culture media was changed out for fresh, drug‐free medium and the cells were allowed to recuperate for another 3 days to a week. The DDP dose was increased from 50 ng/mL to a maximum of 1000 ng/mL (50, 100, 150, 200, 300, 500, 800, and 1000 ng/mL) as described in the previous study 16 . The DDP‐resistant cell strain, labeled as A2780/DDP, was maintained in RPMI1640 complete medium containing 1 µg/mL DDP.…”
Section: Methodsmentioning
confidence: 99%
“…Cancer cell line SKOV3 (ATCC) and cisplatin-resistant cell line SKOV3/DDP were cultured in McCoy’s 5a (Gibco). SKOV3/DDP was created utilizing the previously reported concentration-increasing approach [ 31 ] with cisplatin (C2210000, Merck). They were all supplemented with 10% fatal bovine serun and 1% penicillin-streptomycin (Gibco).…”
Section: Methodsmentioning
confidence: 99%